1997
DOI: 10.1093/humrep/12.6.1343
|View full text |Cite
|
Sign up to set email alerts
|

Endocytotic uptake of small unilamellar liposomes by human trophoblast cells in culture

Abstract: We evaluated the mechanism of uptake of carboxyfluorescein-containing small unilamellar liposomes of different surface charge by trophoblast cells in culture. Carboxyfluorescein-encapsulated neutral liposomes were prepared by using equimolar concentrations of lecithin and cholesterol. Anionic and cationic liposomes were prepared by adding dicetylphosphate and stearylamine. Trophoblast cells from human term placenta were cultured and incubated on the first day at 37 degrees C with liposome-encapsulated carboxyf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…Cationic liposomes have been extensively used in gene delivery due to the electrostatic interaction with the negatively charged DNA [15], [16], [17], [20]. Cationic liposomes help increase the uptake of the entrapped materials through electrostatic interaction between positively charged liposomes and negatively charged cell membrane [15], [16], [17], [21]. In general, the cellular uptake of liposomes occurs through membrane fusion and receptor-mediated endocytosis [15], [16], [17], [22], [23].…”
Section: Discussionmentioning
confidence: 99%
“…Cationic liposomes have been extensively used in gene delivery due to the electrostatic interaction with the negatively charged DNA [15], [16], [17], [20]. Cationic liposomes help increase the uptake of the entrapped materials through electrostatic interaction between positively charged liposomes and negatively charged cell membrane [15], [16], [17], [21]. In general, the cellular uptake of liposomes occurs through membrane fusion and receptor-mediated endocytosis [15], [16], [17], [22], [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, published research on the topic of nanoparticle passage across the placenta is relatively sparse, and several recent reviews [34,37] and Government reports [38] have highlighted this as an area in need of more research. We do not yet have a complete understanding of transplacental uptake and transport mechanisms for all nanomaterials [34], although there is evidence that for some nanoparticles it occurs via an energy-dependent process [7]. However, in preliminary studies, we have shown that uptake of positively charged polymeric nanoparticles by trophoblasts takes place via dynamin-mediated (clathrin-caveolin-dependent) endocytosis [39], supporting other studies indicating Arterial fetal blood (delivered via the umbilical cord) perfuses the placenta through villous capillaries, where gas and nutrient exchange occurs.…”
Section: Nanoparticle Uptake and Passage Across The Placentamentioning
confidence: 99%
“…Placental uptake and transfer is regulated primarily by maternal blood flow and the properties and characteristics of the syncytiotrophoblast membrane. Part of this diagram was adapted from North Carolina State University, WolfWikis [ that nanoparticles enter the placenta via endocytotic uptake [7,34]. It should be noted here that endocytotic uptake into trophoblasts and transplacental transport to the fetus are two distinct processes.…”
Section: Nanoparticle Uptake and Passage Across The Placentamentioning
confidence: 99%
See 1 more Smart Citation
“…Anionic liposomes demonstrate greater stability in solution (Zhigaltsev et al, 2002, Phillips and Heydari, 1996), lead to lower aggregation when compared with neutrally charged liposomes, and have increased endocytosis when compared with cationic (Bajoria et al, 1997) and neutral liposomes. Furthermore, two FDA-approved ophthalmic drugs utilize negatively charged, non-liposomal delivery modalities – Restasis (Allergan, for the treatment of chronic dry eye) and Durezol (Alcon, for ocular inflammation) (Lallemand et al, 2012, de la Fuente et al, 2010).…”
Section: Introductionmentioning
confidence: 99%